Exploring the Experience of Healthcare Workers Who Returned to Work After Recovering From COVID-19: A Qualitative Study - Zhang, Hui; Chen, Dandan; Zou, Ping; Cui, Nianqi; Shao, Jing; Qiu, Ruoling; Wang, Xiyi; Wu, Man; Zhao, Yi (Frontiers in Psychiatry, 2021)
Background: To date, a large body of literature focuses on the experience of healthcare providers who cared for COVID-19 patients. Qualitative studies exploring the experience of healthcare workers in the workplace after recovering from COVID-19 are limited. This study aimed to describe the experience of healthcare workers who returned to work after recovering from COVID-19. Methods: This study employed a qualitative descriptive approach with a constructionist epistemology. Data were collected through semi-structured in-depth interviews with 20 nurses and physicians, and thematic analysis was used to identify themes from the interview transcripts. Results: Three major themes about the psychological experiences of healthcare workers who had recovered from COVID-19 and returned to work were identified: (1) holding multi-faceted attitudes towards the career (sub-themes: increased professional identity, changing relationships between nurses, patients, and physicians, and drawing new boundaries between work and family), (2) struggling at work (sub-themes: poor interpersonal relationships due to COVID-19 stigma, emotional symptom burden, physical symptom burden, and workplace accommodations), (3) striving to return to normality (sub-themes: deliberate detachment, different forms of social support in the workplace, and long-term care from organizations). Conclusions: The findings have highlighted opportunities and the necessity to promote health for this population. Programs centered around support, care, and stress management should be developed by policymakers and organizations. By doing this, healthcare workers would be better equipped to face ongoing crises as COVID-19 continues.